Service e-learning project: state graduation online demo exam - Mandić, Ana (Array, 2011)
The service e-learning project described in this paper presents the online demo exam in informatics designed as a preparatory step for the state graduation. It was created in the midst of turbulence caused by the introduction of the state graduation at the end of secondary education in Croatia. With this project we wanted to engage grammar school students in service e-learning and present them with the opportunity to design their own test materials through the collaboration with college students who are experts in the field. We also aimed to gain our own benefit of connecting the theory learned during the study with new practical experiences while at the same time helping the students to achieve at a high level in the state graduation exam. Finally, since its free available online, our project should benefit everyone who wants to test their knowledge in informatics and/or learn something new in an easy and interesting way.